Calculating Weights of Social Capital Index Using Analytic Hierarchy Process - Nguyen, Phuc Van; Nguyen, Phong Thanh; Nguyen, Quyen Le Hoang Thuy To; Huynh, Vy Dang Bich (International Journal of Economics and Financial Issues, 2016)
This study aims at identifying and ranking social capital indicators in the measurement model for Vietnam context. The analytic hierarchy process is adopted to explore the relative importance of each dimension in the integrated social capital index. The opinions from the in- depth interviews with experts, scholars and practitioners in social capital theory in Vietnam are employed to calculate the indicators’ weights in the model. The empirical findings indicate the superior impact of trust to network in the integrated index. Moreover, bridging and bridging-link are found to be more important than bonding and bonding-link. The result implies the potential of leveraging this resource for the development of individuals and community. Keywords: Economics, Social capital index, Decision making, Analytic Hierarchy Process (AHP), JEL Classifications: A1, C0, K0